Intrapsychical Conflict as a Result of a Professional Stress - Mikhalchuk, Yuliya Aleksandrovna (Psychological Prospects Journal, 2012)
In the article an attempt to define the essence and features of professional stress has been done, the factors of stress in organization has been selected, the states of frustration and intrapsychical conflict as the consequences of a professional stress has been analysed.